(untitled) (Novos Olhares, 2004)
This work investigates the process of constitution of identity in contemporary consumer society, comparing different theoretical approaches and verifying the relevance of these analyzes in the characterization of consumption as an area of demarcation of difference. Discusses the possibility of thinking the difference as the fundamental element of identity in the contemporary world and see it as an operator and producer of individual subjectivity.